The Relation Between The Perception Of Marketing Mix And The Decision To Have Outpatient Treatment In RSIJ Pondok Kopi In 2018 - Nindya Julianingsih; Mustakim Mustakim (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The purpose of this research is to know the relation between the perception of marketing mix and the dedision to have outpatient treatment in RSIJ Pondok Kopi in 2018. This research conducted from April to June 2018 is descriptive-analytic research using the cross sectional design. The research involved 120 outpatients as the research sample using the purposive sampling technique. The research found that as many as 65 respondents ((54.2%)) decided to have an outpatient treatment. It also found that some aspects of marketing mix, which included products, price, place, promotion, human resources and process, were had a significant relation to the decision; meanwhile, the aspect of physical evident was found not to do so. Therefore, it is important that the hospital maintain and improve the quality of its delivered services through providing excellent, professional services and add bench seats on which patients sit waiting for prescribed drugs